Intriguing Revelations from Lithium, Beryllium, and Boron - Ann Merchant Boesgaard (The Astrophysical Journal, 2023)
This is a report on some highlights of research on the rare light elements, lithium (Li), beryllium (Be), and boron (B), that were presented at my Henry Norris Russell Lecture in 2020 January. It is not a comprehensive review of work on these light elements, but contains sections on Big Bang nucleosynthesis of Li and the rarity of these light elements. It includes information on how they are observed, both historically and currently, and the difficulties entailed in determining their abundances. The production of Li, Be, and B is ongoing, so the youngest stars contain the most Li in their atmospheres and they have had less time to destroy it. All three elements are readily destroyed in stellar interiors, but have differing degrees of susceptibility to the particular nuclear fusion reactions which deplete their surface content. This feature makes them remarkably good probes into the otherwise unobservable interiors of stars and provides insights into internal-mixing processes. It also enhances the use of two or more of the three in sorting out the various processes at work in the insides of stars.